Video game-based therapy for the non-dominant hand improves manual skills and grip strength - Bostancı, Hilal; Emir, Ahmet; Tarakçı, Devrim; Tarakçı, Ela (Elsevier, 2020)
The study was designed to investigate the effect of virtual reality-supported training on manual skills and grip strength in the non-dominant hand in healthy participants. Thirty participants were randomized into two groups: ErgoActive group (n = 15) and control group (n = 15). The ErgoActive study group received 8 weeks of training with leap motion controller-based virtual reality games. The training was done 1 day per week for 30 min. The participants' hand function was evaluated using the Jebsen Taylor Hand Function Test (JTHFT), while grip strength was evaluated with a Jamar Hand Dynamometer and Pinchmeter. After 8 weeks, the ErgoActive and control groups had significantly different JTHFT, Jamar and Pinchmeter results (P < 0.05). When leap motion controller-based virtual reality applications are used, healthy subjects have increased manual skills and grip strength in their non-dominant hand. These virtual reality games are an effective and fun way of improving patients' hand functions.
Keywords: Manual Skills; Non-Dominant Hand; Virtual Reality; Upper Extremity; Occupational Therapy